G563(P) Creating an online resource for physicians treating refugees and asylum-seekers. (27th April 2016) - Certic, K; Bennett, T; Baggott, AV
Abstract : Context: We have created a resource available to physicians across all specialties throughout our region. Problem: Over the past several years, an increasing number of refugees and asylum-seekers have arrived in our area. This population has complex physical and mental health needs, and doctors are expected to manage these effectively despite a lack of readily available support. Clinical information, guidelines and support services exist, but can be difficult to identify and access, particularly in time-pressured clinical situations. This can make it challenging for physicians to provide a high standard of care for these patients. Assessment of problem and analysis of its causes: We met with the Service Manager for Refugee Support at our branch of the Red Cross to gather information about the demographics of asylum-seekers and refugees within our area and the specific challenges they face. We also reviewed files of unaccompanied asylum-seeking children within our department and spoke to the named consultant for looked-after children responsible for their care. This helped us identify the issues affecting these patients and areas in which supporting information might be helpful for physicians. We also contacted Heads of School for the other specialties within our Deanery to request feedback and involvement from their trainees. Intervention: We created an online resource for physicians treating asylum-seekers and refugees. This includes links to college and government guidelines; country-specific information, including details regarding endemic diseases, TB and FGM prevalence and languages spoken; contact details of local translators; and links to support networks. We included information for all countries represented within our region. Study design: Strategy for change: We created a website as described above, taking into account feedback from colleagues from our own and other specialties. We shared details of this project with trainees throughout the region via their Heads of School and trainee representatives, and will continue to amend and improve it regularly based on their feedback. Measurement of improvement: We are asking for feedback from anyone who uses the website and have included a contact form on the site for this purpose. We will analyse all feedback we receive and make any necessary amendments to make the site as comprehensive and user-friendly as possible. Effects of changes: We have created a comprehensive new resource which enables local physicians treating refugees and asylum-seekers to access information quickly and easily. This solves the initial problem we identified, of information being difficult to find and access, and provides colleagues throughout the region with easy access to a wide range of relevant information necessary to optimise care of these complex patients. Lessons learnt: We have learned a great deal about the specific problems, both clinical and logistical, involved in treating this particular group of patients. We continue to seek out feedback from colleagues in other specialties and I hope that some of them will become more heavily involved in this project so that we can ensure it is relevant and helpful to all physicians in our area, not just those working in Paediatrics. Message for others: Refugees and asylum-seekers pose a complex set of challenges to physicians who treat them. They may present to a variety of medical specialties, and it is crucial to work with colleagues from within those specialties – as well as local support groups such as the Red Cross – to ensure that we fully understand their health needs and can address them as effectively as possible. We hope that our resource, developed with cross-specialty support, will help colleagues throughout our region to do just that.